The Management of Quality Educator Resources in the Development of the Competitive Islamic Educational Institution in Indonesia - Sari, Linda Nevia; Margrety, Betty; Bahri, Syaiful; Yanto, Murni (The Future of Education Journal, 2025)
Islamic education plays a strategic role in shaping an excellent generation that is not only intellectually intelligent but also possesses a strong personality based on Islamic values. To realize a competitive Islamic educational institution, one of the key factors is the management of high-quality teaching personnel. This management includes planning, organizing, implementing, and evaluating the educators who are competent and highly dedicated. This article aims to analyze various strategies in the management of educational personnel that can lead to the development of competitive Islamic educational institutions in the era of globalization. This study uses a descriptive qualitative approach through literature studies and interviews with administrators of Islamic educational institutions. The results show that developing teachers’ competencies through regular training, objective performance evaluations, and the implementation of appropriate reward systems can enhance the quality of education in Islamic institutions.